Psychological Features of Frustrational Behavior of the Servicemen - Mushkevych, Valentyn (Psychological Prospects Journal, 2020)
The article studies, clarifies and summarizes the materials on the frustrational behavior of servicemen, identifies the psychological features of frustrational behavior, highlights the most characteristic patterns and ways of its course, explores its components that can occur in various areas of personality functioning. Methods. Methods of observation, interviews, questionnaires and testing were used. The main features of frustrational behavior of servicemen are diagnosed with the help of methods «Self-assessment of mental states of G. Eisenko», «Social frustration of L. Wasserman». The Results. It is noted that servicemen are confident in themselves and their abilities, but they are not always ready to accept innovations and have problems adapting to these changes, trying to control the situation that arises themselves. It is established that the servicemen have an average level of manifestation of such psychological states as anxiety, frustration, aggression and rigidity, which gives rise to certain features in the structure of personality and its functioning in the society. It has been proven that the most common type of frustrational behavior of servicemen is extrapunitive reactions with fixation on self-defense, which indicates a tendency to hostility, condemnation, accusations, reproaches and sarcasm; expressed is the active denial of one’s own guilt and attempts to justify oneself. Also pronounced, but less common is the type of extrapunitive reactions with fixation on satisfaction; this type is characterized by the interpretation of frustrating situations as useful or fun. Conclusions. It was found that most servicemen have a very low level of social frustration, which indicates an adequate perception of themselves in the society and normal interaction in the society. It has been proven that such spheres of a person’s life as events in the country, financial situation and the lack of provided services cause a high risk of frustration. It is indicated that the results of this study can be used in the work of a practical psychologist and in such fields as family psychology, general psychology, social psychology, military psychology, occupational psychology.